THE GROWTH OF “PISANG RAJA BULU” PLANLETS IN THE LIGHTING OF INCUBATION ROOMS AND GROWTH REGULATOR AGENTS OF BROWNING PREVENTION BY IN VITRO - Utami Setyawati; Ari Wijayani; Endah Wahyurini (Jurnal Agrivet, 2019)
The aims of this research were to determine the lighting of incubation rooms and browning prevention agents on the growth of “Pisang Raja Bulu” planlets by in vitro and determine whether there is a best interaction between the incubation rooms lighting and the type of browning prevention agents in the growth of “Pisang Raja Bulu” planlets that plants in vitro. This research was conducted in the Biotechnology laboratory of the Faculty of Agriculture, UPN "Veteran" Yogyakarta on June - August 2018. The research method was a laboratory experiment method compiled with the Split Plot Design of two factors. The first factor as a main plot is the incubation room lighting, which is with light for 90 days, without light for 90 days, without light in the first 45 days, and without light in the last 45 days. The second factor as a sub plot is browning prevention agents, named thidiazuron, activated charcoal, and vitamin C. Each combination of treatments was repeated 3 times. The result showed that there was the best combinations of treatments that is all combination of lighting and vitamin C 0,88 mg / l in terms of browning. The first 45 days lighting treatment gave the best result on the percentage of life, plantlet height, number of shoots, number of leaves, root length, and fresh weight. The treatment of vitamin C 0.88 mg / l gave the best result on the percentage of life, plantlet height, number of shoots, root length, number of roots, fresh weight, and dry weight.Keyword: in vitro, lighting, browning, raja bulu banana.